2011
DOI: 10.7205/milmed-d-10-00141
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Health-Promoting Behaviors in Military Spouses During Deployment Separation

Abstract: The purpose of this research was to describe predictors of participation in health-promoting behaviors among military spouses. A total of 105 female spouses of currently deployed active duty military members were surveyed to determine their perceived stress and participation in the health-promoting behaviors of exercise, diet, checkups, substance use/avoidance, social behaviors, stress management/rest, and safety/environmental behaviors. Demographic and deployment information was also collected. Regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Since this time, research designs have varied widely and have extended to include qualitative [171-179], retrospective [77, 180-183], prospective [17, 20, 184-192], and experimental work [193], although most studies are cross-sectional [143, 194-196]. Likewise, studies have narrowed from the examination of stress on the wider scope of health behaviors to a specific focus on the effects of stress on PA and exercise.…”
Section: Resultsmentioning
confidence: 99%
“…Since this time, research designs have varied widely and have extended to include qualitative [171-179], retrospective [77, 180-183], prospective [17, 20, 184-192], and experimental work [193], although most studies are cross-sectional [143, 194-196]. Likewise, studies have narrowed from the examination of stress on the wider scope of health behaviors to a specific focus on the effects of stress on PA and exercise.…”
Section: Resultsmentioning
confidence: 99%
“…Although military spouses have also voiced positive aspects of deployment, a substantial number of spouses experience challenges not only during deployment but also pre-and postdeployment (American Psychological Association, 2007). Spouses cite experiencing increased distress, anxiety, depression, posttraumatic distress, and adjustment diffi culties (Booth, Wechsler, & Bell, 2007;Gewirtz, Polusny, DeGarmo, Khaylis, & Erbes, 2010;Hoge, Auchertonie, & Milliken, 2006;Lapp et al, 2010;Lester et al, 2010;Mansfi eld et al, 2010;Nelson-Goff, Crow, Reisbig, & Hamilton, 2007, 2009Padden, Connors, & Agazio, 2011a, 2011bPatzel, McBride, Bunting, & Anno, 2013;Renshaw, Rodrigues, & Jones, 2008;Sayers, Farrow, Ross, & Oslin, 2009;SteelFisher, Zaslavsky, & Blendon, 2008;Tollefson, 2008). Furthermore, in a study of military spouses with a deployed SM, Padden and colleagues (2011b) reported that perceived stress secondary to deployment accounted for 52% of the variance in mental well-being.…”
Section: Research On Military Spousementioning
confidence: 92%
“…Examining the use of problem-and emotion-focused coping, colleagues (2011a, 2011b) reported that coping styles were also related to various demographic variables such as the spouses and SMs' ages and the number of years on active duty. In general, younger spouses and SMs with less time on active duty used more evasive and emotional coping than confrontive coping methods (Blank, Adams, Kittelson, Connors, & Padden, 2012;Padden, 2011aPadden, , 2011b. One could stipulate that this is related to the lack of knowledge and experience with military resources and other resources.…”
Section: Research On Military Spousementioning
confidence: 94%
“…Some papers did contrast their findings to civilian estimates. Padden et al stated that the prevalence of binge-drinking among current US military spouses/partners (12.4%) was comparable with that among women in the general US population (12.1%)29 and while Blow et al stated that the prevalence of alcohol misuse among current military spouses or partners was slightly higher compared with women from general population studies (10.7% vs 8.4%),25 the authors suggest this may be an artefact of the timing of the survey (the 3 months following the return of Service personnel from deployment) rather than an actual increase in misuse. Self-reported heavy alcohol consumption among spouses or partners of veterans (2%) was reported to be lower than among women of the same age group in the general population (9%),30 suggesting this sample may in fact exhibit healthier lifestyle behaviours than the general population.…”
Section: Resultsmentioning
confidence: 98%
“…Among spouses or partners of currently serving personnel, 3.0%–10.7% met criteria for alcohol misuse using a cut-off of AUDIT score ≥8,24–27 the current gold standard for measuring alcohol misuse28 and an estimated 12.4% met criteria for occasional or regular binge-drinking (≥5 alcoholic drinks on one occasion) 29. Among the veteran community, 2% of spouses/partners of retired military personnel met criteria for heavy drinking according to self-reported monthly or daily consumption30 and 6% met criteria for alcohol abuse or lifetime alcohol dependence 31.…”
Section: Resultsmentioning
confidence: 99%